Game-Based Learning: The Influence of Pictionary Game on Student Engagement and Speaking Proficiency - Dian Hidayah; Andriani Sukmawati (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study investigates the impact of the Pictionary game on student engagement and speaking proficiency among eighth-grade students at SMPN 1 Teminabuan. Utilizing a pre-experimental research design, the study involved a sample of 21 students who participated in Pictionary sessions integrated into their English language classes. The primary instruments for data collection were speaking tests and observation sheets. The aim was to determine whether the game-based learning approach could enhance student engagement and improve their speaking skills. Observation data indicated a significant increase in student engagement during the Pictionary sessions compared to traditional teaching methods. The percentage of students who actively participated in class rose from an average of 40% during traditional lessons to 85% during the Pictionary sessions. Attentiveness, measured by the number of students who remained focused and on task, increased from 50% to 90%. Additionally, interactions among students, including discussions and collaborative problem-solving, were more frequent and dynamic during the game-based activities. The analysis of the speaking test scores revealed a marked improvement in speaking proficiency following the Pictionary intervention. The average pre-test score was 65 out of 100, while the average post-test score increased to 78 out of 100. A paired t-test conducted to analyze the significance of this improvement yielded a p-value of 0.001, indicating that the enhancement in speaking proficiency was statistically significant. In conclusion, the findings demonstrate that the use of the Pictionary game significantly boosts student engagement and speaking proficiency in English language classes. The interactive and enjoyable nature of the game motivates students to participate more actively and provides ample opportunities for practicing speaking skills. These results suggest that incorporating game-based learning strategies, such as Pictionary, can be a highly effective approach to improving educational outcomes in language learning contexts